Endothelin‐1 is a transcriptional target of p53 in epidermal keratinocytes and regulates ultraviolet‐induced melanocyte homeostasis. (24th January 2013) - Hyter, Stephen; Coleman, Daniel J.; Ganguli‐Indra, Gitali; Merrill, Gary F.; Ma, Steven; Yanagisawa, Masashi; Indra, Arup K.
Summary Keratinocytes contribute to melanocyte activity by influencing their microenvironment, in part, through secretion of paracrine factors. Here, we discovered that p53 directly regulates Edn1 expression in epidermal keratinocytes and controls UV‐induced melanocyte homeostasis. Selective ablation of endothelin‐1 (EDN1) in murine epidermis (EDN1ep−/−) does not alter melanocyte homeostasis in newborn skin but decreases dermal melanocytes in adult skin. Results showed that keratinocytic EDN1 in a non‐cell autonomous manner controls melanocyte proliferation, migration, DNA damage, and apoptosis after ultraviolet B (UVB) irradiation. Expression of other keratinocyte‐derived paracrine factors did not compensate for the loss of EDN1. Topical treatment with EDN1 receptor (EDNRB) antagonist BQ788 abrogated UV‐induced melanocyte activation and recapitulated the phenotype seen in EDN1ep−/− mice. Altogether, the present studies establish an essential role of EDN1 in epidermal keratinocytes to mediate UV‐induced melanocyte homeostasis in vivo.